9 - ‘Ties that Bind and Differences that Divide’: Exploring the Resurgence of Ethno-Cultural Identity in Nigeria - Lenshie, Nsemba Edward (Africa Development, 2021)
This article investigates the resurgence of ethno-cultural identity in contemporary Nigeria. The article shows that contestations associated with ethno-cultural identity are not recent, but date back to the creation of the modern state called Nigeria. The article also demonstrates how colonialism fostered various social, economic and political problems in Nigeria and highlights the manner in which the post-colonial political class has fed on the far-reaching effects of colonialism to complicate intergroup relations in the country. The study reveals that Nigeria’s return to civil rule on 29 May 1999, opened the space for the political class to exploit the resurgence of ethnicity and religion in a way capable of jeopardising the corporate existence of the country, especially in the current phase of democratisation. In conclusion, it proffers possible recommendations towards ameliorating the enormous challenges arising from the mismanagement of ethno-cultural identity in Nigeria.